Mapping Innovation Research in Organizations: A Bibliometric Analysis - Peng, Renzhong; Chen, Jingshuang; Wu, Weiping (Frontiers in Psychology, 2021)
This essay conducts a bibliometric study on innovation research in organizations within the three levels (individual, work team, and organizational) by using CiteSpace software to analyzing 6,354 academic articles from the year 2000 to 2020 in four aspects: temporal distribution of published papers, scientific community (countries/regions/cited authors), intellectual structure (cited journals/cited references) and research hotspots. The research ﬁndings show that the total number and the growth rate of publications at organizational level are far higher than the other two levels(individual and work team). The top three countries with the number of publications are The United States, China, and the United Kingdom. The top five highly cited authors are identified and listed from individual, work team, and organizational levels. Academy of Management Journal and Academy of Management Review are the top two highly cited journals at all the three levels (individual, work team, and organizational). The most highly cited articles at the three levels are about topics of linking empowering leadership and employee creativity, team-level predictors of innovation at work, and organizational ambidexterity. The top three research hotspots are identified and listed from individual, work team, and organizational levels. These findings provide snapshots and comparisons of innovation research in management within the three levels (individual, work team, and organizational), which might be beneficial for researchers and scholars to understand and explore innovative behavior in organizations from a multi-level perspective.